2011
DOI: 10.4064/ba59-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication is Discontinuous in the Hawaiian Earring Group (with the Quotient Topology)

Abstract: The natural quotient map q from the space of based loops in the Hawaiian earring onto the fundamental group provides a new example of a quotient map such that q × q fails to be a quotient map. This provides a counterexample to the question of whether the fundamental group (with the quotient topology) of a compact metric space is always a topological group with the standard operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 12 publications
0
51
0
Order By: Relevance
“…For example, consider the Hawaiian earring (HE). Fabel [9] proved that the product q×q : Ω(HE)× Ω(HE) −→ π (HE). Moreover, Fabel [10] showed that for each n ≥ 1 there exists a compact, path connected, metric space X such that multiplication is discontinuous in π qtop n (X, x).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, consider the Hawaiian earring (HE). Fabel [9] proved that the product q×q : Ω(HE)× Ω(HE) −→ π (HE). Moreover, Fabel [10] showed that for each n ≥ 1 there exists a compact, path connected, metric space X such that multiplication is discontinuous in π qtop n (X, x).…”
Section: Resultsmentioning
confidence: 99%
“…Pakdaman et al [24] showed that for a locally (k − 1)-connected space X, π qtop k (X, x) is discrete if and only if X is semilocally n-connected at x (see also [13]). Fabel [9,10] and Brazas [3] presented some spaces for which their quasitopological homotopy groups are not topological groups. Moreover, despite of Fabel's result [9] that says the quasitopological fundamental group of the Hawaiian earring is not a topological group, Ghane et al [14] proved that the topological kth homotopy group of an k-Hawaiian like space is a prodiscrete metrizable topological group, for all k ≥ 2.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that π 1 (X, x 0 ) is a quasitopological group in the sense that inversion is continuous and the group operation is continuous in each variable. However, π 1 (X, x 0 ) can fail to be a topological group [4,13,14]. A general study of fundamental groups with the quotient topology appears in [7].…”
Section: Application To Topologized Fundamental Groupsmentioning
confidence: 99%
“…There are several examples which illustrate that π qtop 1 (X, x 0 ) does not need to be a topological group even if X is a compact metric space (see [8,9]). Calcut and McCarthy [7] proved that the quotient topology induced by the compact-open topology of the fundamental group of a locally path connected and semilocally simply connected space is discrete which implies that π qtop 1 (X, x 0 ) is a topological group.…”
Section: On the Whisker Topology And Sltl Spacesmentioning
confidence: 99%